DERAJAT LATERITISASI DAN PENGAYAAN UNSUR FE-NI-CO PADA BATUAN HARSBURGIT DI PULAU SEBUKU, KALIMANTAN SELATAN: DEGREE OF LATERITIZATION AND ENRICHMENT OF FE-NI-CO ELEMENTS IN HARSBURGITE ROCKS ON SEBUKU ISLAND, SOUTH KALIMANTAN - Fasya Zahra Fauziyyah Ramdani; Ayumi Hana Putri Ramadhani; Andhi Cahyadi; Ernowo; Wahyu Widodo (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2023)
The tropical climate in Indonesia causes a high level of chemical weathering or lateritization of ultramafic rocks which results in the enrichment of economic elements such as Fe, Ni and Co. These elements accumulate in the limonite and saprolite zones. This research was conducted on Sebuku Island which composed of ultramafic rocks, especially harzburgite. This study aims to determine the effect of the degree of lateritization in the limonite, saprolite and bedrock zones on the enrichment of economic elements. A number of 95 samples collected from 9 drill holes and analyzed using XRF to determine the main elements and economic elements. The degree of lateritization is calculated from the SiO2 content divided by the total accumulation of SiO2, Al2O3 and Fe2O3 resulting the S/SAF index which describes the intensity of the chemical reaction. The lowest value of the S/SAF index indicates a higher degree of lateritization. Each limonite, saprolite and bedrock zone has S/SAF index values ​​ranging from 0.16 to 58 (strong lateritization), 0.27 to 0.85 (medium lateritization-kaolinization) and 0.77 to 1.24 (mother rock). The zone with a strong degree of lateritization contains Fe levels between 36% to 51%, Ni 0.80% to 1.38% and Co 0.07% to 1.17%. The bedrock contains 4.86% to 7.99% Fe, 0.20% to 1.76% Ni and 0.005% to 0.015% Co. The degree of lateritization in the limonite zone is higher than the saprolite and bedrock zones. This is caused by the decomposition of silica minerals to form the iron and aluminum oxide-hydroxide bearing minerals. The degree of lateritization has a positive correlation with the enrichment of Fe and Co. However, the distribution of high Ni not correlated with the index of lateritization.